"Det fanns ju bara indicier" - En studie om grundskolelärares reflektioner kring anmälningsplikt - Halling,Martin; Körner,Malin (2011)
Authors: Malin Körner and Martin Halling Title: “Det fanns ju bara indicier” - En studie om grundskolelärares reflektioner kring anmälningsplikt Supervisor: Tove Harnett Among others, elementary school teachers in Sweden are obligated by law to report to the social services if they suspect that a child is maltreated in one way or another. Nevertheless, research indicates that only few of the suspected cases are actually reported. Also, the law and the predatory works are subject to different interpretations: What is included in the term ”maltreated”? What constitutes a suspicion? When is a report to be filed - in reality? We chose to interview seven elementary school teachers in the form of semi-structured interviews. The aim of this study was to examine how they reflect about their obligation to report, and how we could possibly explain or justify why reports are often not filed. To arrange our material and find patterns, we used a scheme of coding. We coded upon: what the informants included in the term “children that are maltreated”, what roles that where categorized, and what impediments and solutions the informants described in the report process. Furthermore we used social constructive theory to analyse what the informants apprehended as real and true from their concept of reality. For one thing, we found that the informants described the home arena and the school arena as separate territories with different authorities. The teachers experienced that they were not to intervene in private family matters. Roughly speaking, this is one possible explanation why reports are not made although it’s suspected that a child is being maltreated. The informants also described the social services in quite negative terms. The social services didn’t come across as gaining the informants’ confidence. This is another possible way to get an understanding of why teachers are lacking in their propensity to report.
Keywords: Maltreated children; obligation to report; school; social services